MANAJEMEN PENDIDIKAN KARAKTER DALAM RANGKA PENINGKATAN MUTU PROSES DAN HASIL BELAJAR SISWA DI SMA NEGERI 2 GRABAG KABUPATEN MAGELANG (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to determine the management (planning, organizing, implementation and evaluation) character education in order to improve the quality of teaching and student learning outcomes at SMAN 2 Grabag Magelang regency This study is a qualitative study conducted in SMAN 2 Grabag Magelang regency. Data collection technique used observation, interview and document research. The subjects of the study was the principal, vice principal of curriculum affairs, vice principal Infrastructure affairs, student affairs vice principal, vice principal affairs public relations, Head of Administration, teachers and students. Data validation was done through the triangulation of data and triangulation techniques. The results of the research showed that: 1. Management of character education in conducted to improve the quality of teaching and learning outcomes; a. Planning is already well underway, proved all the activities have been programmed. b. Organizing is good, where the responcibility is in the hands of principals who assisted the vice principal of curriculum affairs, student affairs, business infrastructure, business public relations, and the Head of Administration, c. Implementation of character education goes well in accordance with the programmed, d. evaluations that are conducted there daily, weekly and semester. 2. Factors supporting character education management in order to improve the quality of teaching and learning outcomes include school programs, competent teachers, parents, and school infrastructure. 3. Factors inhibiting character education management in order to improve the quality of teaching and learning outcomes include some means are insufficient / no, the majority of parents were less supportive of the school program, as well as the majority of human resources (HR) is less supportive of the program habituation